2012
DOI: 10.1186/1471-2415-12-13
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Phacoemulsification in patients with and without Pseudoexfoliation syndrome in Kashmir

Abstract: BackgroundThe aim of the study is to compare the outcome of phacoemulsification in patients with and without pseudoexfoliation syndrome in Kashmir.Methods200 patients were prospectively evaluated and divided into 2 groups. Group 1 comprised 100 cases with pseudoexfoliation and Group 2 (control) 100 cases without pseudoexfoliation. Phacoemulsification with posterior chamber intraocular lens implantation was performed by 3 surgeons. Intraoperative and postoperative observations were made in both the groups at re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
16
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 20 publications
7
16
1
1
Order By: Relevance
“…Patients with pseudoexfoliation syndrome were significantly older, had smaller pupil diameter and higher IOP than controls. These findings are similar to recently published study results [13]. Out of 300 patients with cataract and pseudoexfoliation syndrome, 30 (10%) had capsular glaucoma, which is statistically significantly more frequent than in controls.…”
Section: Discussionsupporting
confidence: 92%
“…Patients with pseudoexfoliation syndrome were significantly older, had smaller pupil diameter and higher IOP than controls. These findings are similar to recently published study results [13]. Out of 300 patients with cataract and pseudoexfoliation syndrome, 30 (10%) had capsular glaucoma, which is statistically significantly more frequent than in controls.…”
Section: Discussionsupporting
confidence: 92%
“…Intraoperative difficulties in cataract surgery in patients with PXF syndrome have been reported in various studies. [946474849] However, Shastri and Vasavada have reported that intraoperative performance of cataract surgery in PXF eyes is comparable to that in non-PXF eyes. [50] In our study, intraoperative difficulties occurred in 62 eyes (27.4%) while performing cataract surgery by phacoemulsification.…”
Section: Discussionmentioning
confidence: 99%
“…[51] The common intraoperative complication observed in our study was zonular dehiscence ( n = 18, 8%), consistent with the findings in several studies. [4647484951] This complication is expected in patients with PXF syndrome, particularly in cases of high-grade cataract. Another complication is non-dilating pupil or decreased pupil dilation during the surgery.…”
Section: Discussionmentioning
confidence: 99%
“…and Sufi found no correlation was found between PCR and the presence of PXM during phacoemulsification. [78] Pterygium involving the cornea, corneal opacity, glaucoma, and chronic uveitis were not associated with intraoperative complications in our study. Pterygium and corneal opacities extending to the visual axis may hamper the view for capsulorhexis and phacoemulsification, but this did not cause an increase in complications.…”
Section: Discussionmentioning
confidence: 46%